Compound climate events threaten tropical semi-enclosed marine ecosystems - Éva E. Plagányi; Laura K. Blamey; Rob Kenyon; Stephanie Brodie; Roy Aijun Deng; Denham Parker; Richard D. Pillans; Nicole E. Murphy; Margaret Miller; Amelia A. Desbiens; Sean Pascoe; André E. Punt (Science, 2026)
Anthropogenic ocean warming affects ecosystem functioning but is not necessarily the primary climate driver regulating tropical seas. Tropical semi-enclosed marine ecosystems are poorly understood, geographically distinct, and influenced by compounding impacts from global warming, cyclones, monsoons, freshwater influx, and massive sea-level and circulation variability. We unify climate risk understanding of these large-scale integrated ocean-atmosphere-biological systems, showing that compound climate events expose resident species to larger, prolonged fluctuations, causing reconfigured spatial patterns and lack of sustained hydrological connectivity. We attribute changes in species’ abundance in these systems to complex and cumulative combinations of extreme temperatures, exposure, turbidity, and hydrologic connections. We describe evidence of such climate-induced physical and biological regime shifts in tropical marine ecosystems in northern Australia and identify implications for other systems.